Water, Energy, and Environment A Primer - Hoffman, Allan (IWA Publishing, 2019)
The book presents a clear explanation of the inextricable linkages among water, energy, and environment issues - the water/energy/environment nexus. Early chapters discuss the current water, energy, and environment contexts in detail, including an overview of global water issues, the importance of energy efficiency, traditional energy and emerging renewable energy technologies, global warming and climate change and other water- and energy-related environmental issues (e.g., water and air contamination, oil spills, radioactive waste storage, environmental impacts associated with solar, wind, hydropower, and biomass energy), the importance of recognizing and dealing with the nexus as well as policy implications and recommendations for moving forward. Insight is given into the policy process associated with the nexus, policy history, policy options, and steps people and institutions can take to address issues such as climate change, access to clean water, and energy poverty.